2020
DOI: 10.1177/1932202x20918203
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Exceptional Talent in Science, Technology, Engineering, and Mathematics: Increasing Diversity and Assessing Creative Problem-Solving

Abstract: In the Cultivating Diverse Talent in STEM project, funded by the National Science Foundation in the United States, new assessments were developed, field tested, used to identify students with exceptional talent in science, technology, engineering, and mathematics (STEM), and compared with existing methods (grade point average [GPA], letters of recommendation, self-statements). Students identified by both methods participated in an internship program in laboratories of scientists on the campus of an R1 universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(67 citation statements)
references
References 128 publications
(257 reference statements)
1
64
0
2
Order By: Relevance
“…Considering the fact that GPAs are on a 4-point scale, the difference between an average of 3.9 and an average of 3.0 is educationally and statistically significant. Maker (2020) found significant differences between students selected by the DISCOVER problem solving assessments and those selected by conventional methods in three areas: GPA, ethnicity, and parent level of education. She concluded that the differences in ethnicity could not be attributed to the selection methods because of the makeup of the partner schools (high percentages of Hispanic and American Indian students); however, GPA and parent level of education could be attributed to the differences in methods.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…Considering the fact that GPAs are on a 4-point scale, the difference between an average of 3.9 and an average of 3.0 is educationally and statistically significant. Maker (2020) found significant differences between students selected by the DISCOVER problem solving assessments and those selected by conventional methods in three areas: GPA, ethnicity, and parent level of education. She concluded that the differences in ethnicity could not be attributed to the selection methods because of the makeup of the partner schools (high percentages of Hispanic and American Indian students); however, GPA and parent level of education could be attributed to the differences in methods.…”
Section: Discussionmentioning
confidence: 84%
“…The conventional method, which had previously been used as the only method of selection, consisted of grade point average (GPA), teacher recommendation, and self-statement. Overall results are provided in another publication (Maker, 2020). Descriptions of the new performance assessments used in the selection process for M2 students are provided in other publicatons: concept maps (Maker & Zimmerman, 2020), math (Bahar & Maker, 2020), life science performance assessment (Zimmerman et al, 2020), physical science performance assessment (Alfaiz et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations